Geosocial Networking App Use Among Men Who Have Sex With Men in Serious Romantic Relationships - Macapagal, Kathryn (Arch Sex Behav, 2016)
Geosocial networking (GSN) mobile phone applications (“apps”) are used frequently among men who have sex with men (MSM) to socialize and meet sexual partners. Though GSN apps are used by some MSM in partnered relationships, little is known about how the use of GSN apps among MSM in serious romantic relationships can influence couples' sexual and relationship health. MSM in serious relationships (N = 323; M age = 40 years) were recruited through a popular GSN app for MSM. Participants completed open-ended items regarding the costs and benefits of app use to their relationships, discussions of app use with their partners, and preferences for relationship education related to app use. Reported benefits of app use included improving sex and communication with one's primary partner and fulfilling unmet sexual needs. Although approximately half had not discussed app use with their partners, citing app use as a “non-issue,” many cited various drawbacks to app use, including jealousy and being a distraction from the relationship. Few described sexual health concerns as a drawback to meeting partners through apps. Regarding relationship education preferences, most wanted help with general communication skills and how to express one's sexual needs to a partner. Although GSN app use can enhance relationships and sex among partnered MSM, unclear communication about app use may contribute to negative relationship outcomes and could prevent partners from having sexual needs met. Relationship and sexual health education programs for male couples should consider addressing social media and technology use in their curricula.